Proprioception over Dogma: Sources of Authority and Standards of Orthopraxy in Iyengar Yoga - Ciołkosz, Matylda (Religions of South Asia, 2018)
The purpose of the article is to discuss the factors influencing the ongoing developments in Iyengar Yoga (IY) asana practice. The hypothesis is that within IY the power of authority, rather than being associated with the guru and his lineage (parampara), is located within the body and associated with individual proprioceptive experience. Despite its apparent dogmatism, manifesting in rigorous focus on minute detail and strong notions of orthopraxy, Iyengar's system has undergone major changes ever since the publication of Light of Yoga in 1966. Since Iyengar's death in 2014, the need for constant innovation seems to have increased. The author argues, that the plasticity of the method is inherent in its very foundations. Treating asanani--and sequences thereof--as higher-order structures built of repetitive minimal units (singular motor patterns and body-part configurations) allows for considerable freedom in asana practice without jeopardizing orthoperformance. The stress lain on the detailed proprioceptive experience during practice results in locating authority in the experience itself, and in frequent modifications of asana variations based on this authority. The discussion is based on in-depth analysis of the structure of IY practice and of textual material.